Health Promotion in Israeli Colleges of Higher Education—The Example of Oranim College of Education - Hof-Nahor, Irit; Biswas, Seema (Frontiers in Public Health, 2020)
Oranim College of Education in northern Israel responded to a countrywide call for integration of health promotion into the culture and curriculum of teacher-training to meet Ministry of Education policy goals for health promotion in schools and kindergartens across Israel. This paper outlines the changes made at the college over three years:  commitment of college executives to the health promotion program  appointment of a health leader (health promotion coordinator)  staff and student engagement in change  rededication of college resources toward healthy lifestyles and learning  promotion of healthy eating and exercise  overhaul of the cafeteria  changes in teaching style  open-air classes  new courses  health promotion in kindergartens by teachers-in-training  deeper community interaction